2021
DOI: 10.1002/celc.202100408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alkali Cation Identity on the Conversion of HCO3 to CO in Bicarbonate Electrolyzers

Abstract: The reduction of CO 2 to CO from a bicarbonate feedstock offers an opportunity to directly use aqueous carbon capture solutions, while bypassing ex-situ energy-intensive gaseous CO 2 regeneration. In this study, we resolved how the electrolyte cation identity (Li + , Na + , K + , Cs + ) affects the two reactions that make bicarbonate electrolysis possible: (i) the production of insitu CO 2 formed through reaction of HCO 3 À (from the catholyte) with H + (sourced from the membrane); and (ii) the electroreductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…1a). [16][17][18][19][20][21][22][23][24][25][26][27] However, inferior selectivity toward CO or formate has been exhibited compared with that of the conventional CO 2 -fed electrochemical reduction reaction (CO 2 RR). 28 The electrocatalytic activity is determined by the charge transfer at the electrode-electrolyte interface, which necessitates the thorough investigation of cCO 2 RR in terms of the interactions with the absorbent medium to improve the conversion activity.…”
Section: Introductionmentioning
confidence: 99%
“…1a). [16][17][18][19][20][21][22][23][24][25][26][27] However, inferior selectivity toward CO or formate has been exhibited compared with that of the conventional CO 2 -fed electrochemical reduction reaction (CO 2 RR). 28 The electrocatalytic activity is determined by the charge transfer at the electrode-electrolyte interface, which necessitates the thorough investigation of cCO 2 RR in terms of the interactions with the absorbent medium to improve the conversion activity.…”
Section: Introductionmentioning
confidence: 99%
“…In all of the above scenarios, however, researchers have separately determined the importance of having alkali cations present at the electrode–electrolyte interface when performing ECO2R. Unlike alkaline conditions where high ECO2R Faradaic efficiencies can be achieved over a range of cation concentrations, recent work in acidic or neutral pH cathode conditions highlights that a special consideration of cation concentrations is required to achieve high CO 2 reduction selectivities. Combining these observations with previous BPMEA demonstrations that have traditionally suffered from poor CO 2 reduction selectivities, we hypothesized that the low selectivity in a BPMEA system could be overcome by increasing cation concentrations at the cathode. ,, Thus, if the low parasitic CO 2 loss of BPM’s can be achieved simultaneously with improved CO 2 reduction performance, high CO 2 utilization efficiencies would be possible as a result.…”
mentioning
confidence: 98%
“…163,164 Actually, it has been shown that cation crossover from the anode to the cathode can improve the electroreduction performance, but the formation of a precipitate makes the flow cell unstable during long-term operation. 165–168 To overcome this contradiction, Janáky et al 169 proposed an operando activation and regeneration process, where the cathode of a membrane zero-gap flow cell was periodically infused with alkali cation-containing solutions with good wetting properties. The activation was repeatable and the flow cell obtained a high performance with a CO partial current density of nearly 420 mA cm −2 for over 200 h.…”
Section: Electrolyzer Designmentioning
confidence: 99%